Peran layanan konseling individu pendekatan behavioristik terhadap minat pembelajaran daring pada siswa kelas VIII smp negeri 2 kebakkramat tahun 2021/2022 - Oktavia, Laila (Program Studi Bimbingan dan Konseling FKIP Universitas Slamet Riyadi, 2023)
Abstract: In 2019 there was an outbreak very deadly disease Indonesia and all countries in the world to lock down or quarantine, this resukt in all schools in Indonesia to be temporarily closed. schools implemented the learning trought learning from home. From here, many problems arose that were experienced by students, especially those related to learning interest in online learning during the covid-19 pandemic. This was also felt by BK teachers who wanted to provide Guidance and Counseling Services. They also experienced many obstacles during the covid 19 pandemic. Therefore, the researcher wants to know more about the role of individual counseling services with a behavioristic approach to online learning interest in student in class VIII at SMP N 2 kebakkramat during the current pandemic. This study aimed to describe the role of Individual Counseling Services with a behavioristic approach to online leaning in student in class VIII at SMP Negeri 2 Kebakkramat in the 2021/2022 academic year. This type of research uses descriptive method. This research wasconducted at SMP Negeri 2 Kebakkramat. The research subjects were 1 BK teacher and 7 students. Data collection techniques were trought observation, interviews, and documentation. To check the validity of the data was to extended the observations and triangulation and persistence of observations. The results of the study were analyzed by going trought the stages of data reduction, data presentation, and conclusions or verification. The results showed that the role of providing individual counseling services with a behavioristic approach to class VIII was very instrumental in solving students' problems about learning interest. Because it could be seen how the student’s interest in learning has decreased in interest in learning. It could be seen by how the BK teacher implemented the individual counseling service to students. From carrying out these counseling service aktivities, BK teacher could find out thr supporting factors and inhibiting factors experienced by students in lerning during thisandemic so that BK teacher was able to make decisions to slve problems faced by students related to the deckine interest ini online learning. Keywords: Roles, Individual Counseling Services with Behavioristic Approach, Students’ interest in Online.